Regulatory Disruption of Online Business Licensing (A Case Study of Legal and Ethical Challenges) - Ngaisah, Siti (Faculty of Law, University of Muhammadiyaha Surabaya, 2024)
Regulatory Disruption in Online Business Licensing has become a major subject in the modern legal and ethical landscape. The study highlights emerging regulatory challenges related to online business licensing, examining the impact of such disruptions on legal arrangements and emerging ethical issues. The cases discussed illustrate the complexities faced in adapting regulations to the dynamics of online business, including data privacy issues, transaction security, and consumer protection. Legal challenges include adapting regulations to technological innovation, while ethical challenges highlight openness, honesty, and protection of individual rights in an evolving online business environment. By analyzing the impact of disruption on online business licensing regulations, this study aims to identify solutions and approaches that can consider and balance legal and ethical aspects in regulating today's digital business world. This research uses a qualitative approach which is also intended to collect and utilize and distribute all information related to the subject matter raised.